Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - Barth, John A.; Allen, Susan E.; Dever, Edward P.; Dewey, Richard K.; Evans, Wiley; Feely, Richard A.; Fisher, Jennifer L.; Fram, Jonathan P.; Hales, Burke; Ianson, Debby; Jackson, Jennifer; Juniper, Kim; et al. (Frontiers in Marine Science, 2019)
The ocean knows no political borders. Ocean processes like summertime, wind-driven upwelling stretch thousands of kilometers along the Northeast Pacific (NEP) coast. This upwelling drives marine ecosystem productivity and is modulated by weather systems and seasonal to interdecadal ocean-atmosphere variability. Major ocean currents in the NEP transport water properties like heat, fresh water, nutrients, dissolved oxygen, pCO2 and pH close to shore. The eastward North Pacific Current bifurcates offshore in the NEP, delivering open-ocean signals south into the California Current and north into the Gulf of Alaska. There are a large and growing number of NEP ocean observing elements operated by government agencies, Native American Tribes, First Nations groups, not-for-profit organizations, and private entities. Observing elements include moored and mobile platforms, shipboard repeat cruises, and land-based and estuarine stations. A wide range of multidisciplinary ocean sensors are deployed to track, for example, upwelling, downwelling, ocean productivity, harmful algal blooms, ocean acidification and hypoxia, seismic activity and tsunami wave propagation. Data delivery to shore and observatory control are done through satellite and cell phone communication, and via seafloor cables. Remote sensing from satellites and land-based coastal radar provide broader spatial coverage. Numerical circulation and biogeochemical modeling complement ocean observing efforts. Models span from the deep ocean into the inland Salish Sea and estuaries. NEP ocean observing systems are used to understand regional processes and, together with numerical models, to provide ocean forecasts. By sharing data, experiences and lessons learned, the regional ocean observatory is better than the sum of its parts.